Stability and activity of Zn/MCM-41 materials in toluene alkylation: microwave irradiation vs continuous flow - Carraro, Paola María (2019)
Zn/MCM-41 mesoporous materials have been prepared via classic wet impregnation, employing zinc nitrate as precursor and tested for activity and stability in the Friedel-Crafts alkylation of toluene with benzyl chloride under microwave irradiation and continuous flow. The modified materials were characterized by means of a number of analytical techniques, and surface and textural properties were thoroughly checked. Materials containing the highest Zn loading (15 wt %) provided full conversion after 5 minutes reaction under microwave irradiation (300 W, 120 °C). Materials were proved to be stable and reusable for several cycles with an optimum performance under continuous flow conditions.